2018
DOI: 10.1111/resp.13433
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to temperature variation exacerbates airway inflammation through TRPA1 in a mouse model of asthma

Abstract: Background and objective Studies from epidemiology suggest that ambient temperature is one of the underlying triggers and potential causes of asthma. The aim of this study was to examine the impact and the molecular mechanism of temperature‐invoked airway inflammation using an experimental model of asthma in BALB/c mice. Methods Mice were exposed to different temperature conditions (steady 26°C, 26°C/18°C cycle, 26°C/10°C cycle) and received sensitization and challenge of ovalbumin (OVA) during a 21‐day period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…7D, E, and F). These observations corroborated with those of previous studies, thereby demonstrating that repeated cold exposure could exacerbate asthma in mice (10,11).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7D, E, and F). These observations corroborated with those of previous studies, thereby demonstrating that repeated cold exposure could exacerbate asthma in mice (10,11).…”
Section: Discussionsupporting
confidence: 91%
“…Liao et al suggested that airway in ammation and hyper-responsiveness can be prominently relieved by housing asthmatic mice at a thermoneutral temperature of 30°C, compared with a standard temperature of 20°C (9). Moreover, Deng et al and Du et al showed that repeated cold exposure at 10°C can aggravate asthmatic symptoms in mice (10,11). However, the exact mechanisms underlying the development of asthma under cold conditions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The transient receptor potential A1 (TRPA1) has been implicated in both asthma and cough due to cold air . Using an ovalbumin (OVA) model of allergic asthma, researchers demonstrated that repeated exposure to cold air worsened airway inflammation, increased airway hyperreactivity and led to up‐regulation of TRPA1 . Administration of a TRPA1 channel blocker reduced expression and the asthma‐like features that had been seen.…”
Section: Mechanisms Of Diseasementioning
confidence: 99%
“…In a recent publication in Respirology, Du et al . use a novel approach of fluctuations in temperature (26/18°C, 26/10°C), in concert with a well‐established, allergen‐induced, aluminium hydroxide/ovalbumin Th2‐driven allergic airways disease model.…”
mentioning
confidence: 99%